Post-harvest handling of cut flowers – a way to minimize market glut - Kumari, Meenu; Swaroop, Kishan; Saha, Tarak Nath; Kumar, Ramesh (Indian Horticulture, 2019)
Flowers are precious and unique gift of nature. They adorn the world with their aesthetic and economic properties. The cut flowers are highly perishable commodity for which longevity of cut stems is determined by both pre- and postharvest factors. The post-harvest losses of flowers are up to 40%. It can be reduced by using easily available preservatives, sealing flowers inside low density polyethylene film and cold storage. This avoids gluts and distress sale. Hence, it enhances growers income and even small growers can adopt this technology.